Bis-anthracene derived bis-pyridine: selective fluorescence sensing of Al3+ ions. (18th January 2019) - Bhuvanesh, N.; Suresh, S.; Kannan, K.; Rajesh Kannan, V.; Maroli, Nikhil; Kolandaivel, Ponmalai; Nandhakumar, R.
Abstract : A novel bis-anthracene molecule linked to bis-pyridine by xylylene dibromide (APC ) was synthesized as a potent sensor for the detection of Al 3+ ions. Abstract : A novel bis-anthracene molecule linked to bis-pyridine by xylylene dibromide (APC ) was synthesized as a potent sensor for the detection of Al 3+ ions. ReceptorAPC exhibits high affinity towards Al 3+ ions through fluorescence 'off–on' behaviour in HEPES-buffered THF–H2 O (1 : 1, (v/v) HEPES = 50 mM, pH = 7.4) solution with a detection limit of 0.89 × 10 −6 M. The affinity between receptorAPC and Al 3+ ions can be attributed to the photoinduced electron transfer (PET) mechanism. Furthermore, the receptorAPC can be employed for the detection of Al 3+ ions in various effluent water samples and in microbial bioimaging.